Locrine - Shakespeare, William, 1564-1616 (Salt Lake City, UT : Project Gutenberg, 1998)
"Locrine" by William Shakespeare is an Elizabethan play published in 1595. It dramatizes the legendary Trojan founders of ancient Britain, following the aged Brutus as he divides his kingdom among his three sons before death. When invading Scythians threaten the realm, revenge and tragedy unfold through five acts of Senecan drama. Each act opens with the goddess Atë presenting symbolic dumbshows of mythological violence. The play weaves together dynastic conflict, arranged marriage, warfare, and ghostly vengeance in a foundation myth for England itself. (This is an automatically generated summary.)
Shakespeare apocrypha - work questionably attributed to Shakespeare and others. See https://en.wikipedia.org/wiki/Shakespeare_apocrypha for more information
Wikipedia page about this book: https://en.wikipedia.org/wiki/Locrine
Release date is 1998-11-01
the PG Shakespeare Team, a team of about twenty Project Gutenberg volunteers
Keywords: Tragedies (Drama); Britons -- Drama